RESPON PERTUMBUHAN BIBIT SETEK VANILI (Vanila planifolia) TERHADAP APLIKASI BEBERAPA JENIS ZAT PENGATUR TUMBUH ALAMI - Yulius Gae Lada; Diana Moghom; Apik Nusantari; Victor H. Rimindubby (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2026)
Vanilla is a high-value plantation commodity prized for its vanillin content, an essential raw material in the food, beverage, perfume, and cosmetic industries. This study aimed to examine the growth response of vanilla stem cuttings to various natural Plant Growth Regulators (PGR) and identify which organic source yields the most effective results. The research was conducted at the Greenhouse of the Faculty of Agriculture, Forestry, and Marine Sciences, Ottow Geissler University, Papua. The study employed a Completely Randomized Design (CRD) consisting of five treatments with seven replications each. The treatments included: A1 (Control), A2 (Coconut water 500 ml/l), A3 (Bamboo shoot extract 4 ml/l), A4 (Rice washing water 130 ml/l), and A5 (Red onion extract 10 ml/l). Vanilla cuttings were immersed in the respective solutions for 10 hours prior to planting in polybags. Parameters measured included survival percentage, shoot length, leaf count, and root length. Data were analyzed using ANOVA, followed by the Least Significant Difference (LSD) test where applicable. The results indicated that the application of different natural growth regulators did not produce significantly different responses, as all treatments yielded equally positive outcomes. However, A2 (Coconut water) emerged as the most effective treatment across all parameters, achieving a 100% survival rate, a shoot length of 11.40 cm, an average of 5.71 leaves, and a root length of 30.47 cm.